Cenários de intensificação da pecuária de corte e sua sustentabilidade no bioma amazônico - Alves, Thaís Emanuele Lima (2021)
Beef livestock is one of the main activities in Brazil that boosted the country's GDP growth, but with the expansion of agricultural production, in some places in Brazil, mainly in the Amazon Biome, this opening of areas is still done in a extractive cases in extractive cases in many pastures and soil. With the production of consumers, entities linked to the environment and market, especially beef producers by society and the Amazon region, seek production in a way that meets current needs for production in a way that meets current needs. The use of models, mainly to assess environmental impacts, is one of the alternatives that can help the producer in decision-making on the rural property. The Integrated Farm System Model is a model capable of estimating the biological and physical processes of the farm integrating the climatic conditions of the region for a period of many years. The delivery as a model of the variants, and output mainly as variables. The objective of the present work was evaluated in three scenarios for finishing beef cattle in a cooperative located in the Amazon biome: finishing exclusively with o (conventional system); termination in confinement; finishing to pasture with supplementation. The collection of meteorological data on the property was carried out in the period of 11 years between January 2007 and December 2018 and with this information, the performance of the finishing scenarios to pasture, confinement and pasture with supplementation were simulated. As the simulations indicate, the more a system with greater adoption of technologies in a certain area, the greater the cost, but there is an increase in production efficiency and the environmental impacts per kg of product produced are smaller in proportion to the way of creation commonly carried out. in the country. The model was efficient to represent the scenarios and can still be used under other conditions imposed in the region of the country.